Outbreak of type C botulism in aquatic birds on the Nahuel Huapi Lake and National Park Area, Argentina - Rosciano, Natalia Gimena (2021)
An outbreak of avian botulism type C occurred at the Kelp Gull (Larus dominicanus) colonies located at the Nahuel Huapi National Park and lake area in Argentina, at the end of the breeding season, during austral summer 2020. While conducting fieldwork, birds were observed with paralysis of the lower and upper limbs, and dead birds were found in a sitting down position with no signs of having been attacked. We collected blood and tissue samples from eight Kelp Gulls and one Ashy-headed Goose (Chloephaga poliocephala) for toxicological analysis. One sample of Ashy-headed Goose resulted positive for botulinum toxin type C. Diseases like botulism are usually lethal for wildlife and have important effects on bird populations. Though the impact on the Kelp Gull colonies did not seem to be of great concern (~2.3% of the population affected), specific research into the source of the toxin and the initiating conditions are required to understand the potential threats to the environment and to different bird populations that live in this area. This would be key for aquatic bird species such as the Ashy-headed and the Upland Goose (C. picta), both considered threatened in Argentina.